Evaluation of Biosafety, Antiobesity, and Endothelial Cells Proliferation Potential of Basil Seed Extract Loaded Organic Solid Lipid Nanoparticle - Subash-Babu, Pandurangan; Al-Saran, Nada; M. Alshammari, Ghedeir; Naif Al-Harbi, Laila; Hussain Alhussain, Maha; Shamlan, Ghalia; Abdulaziz AlSedairy, Sahar; Abdullah Alshatwi, Ali (Frontiers in Pharmacology, 2021)
The present study aimed to synthesize solid lipid nanoparticles to enhance liposome-assisted intracellular uptake of basil seed active components in adipocytes and vascular smooth muscle cells to attain increased bioavailability. To obtain solid lipid nanoparticle (SLNp), the water phase containing basil seed extract (BSE) was encapsulated with lipid matrix containing chia seed phospholipids using homogenization and cold ultra-sonication method. The physicochemical characterization of basil seed extract loaded solid lipid nanoparticles (BSE-SLNp) has been analyzed using Zetasizer, FT-IR and TEM. The BSE-SLNp showed an average diameter of 20 to 110 nm on the day of preparation and it remains the same after 60 days of storage. The cytotoxicity assay confirmed that the BSE-SLNp did not produced toxicity in hMSCs, preadipocytes or human umbilical vein endothelial cells (HUVECs) until the tested higher dose upto 64 μg/ml. During effective dose determination, 4 μg/ml of BSE-SLNp confirmed non-toxic and enhanced metabolic function in hMSCs, preadipocytes and HUVECs. Biosafety assay confirmed normal nuclear morphology in PI staining and high mitochondrial membrane potential in JC-1 assay with in 48hr in hMSCs. The maturing adipocyte treated with 4 μg/ml of BSE-SLNp significantly increased the mitochondrial efficiency and fatty acid beta-oxidation (PPARγC1α, UCP-1 and PRDM-16) related gene expression levels. Oxidative stress induced HUVECs treated with 4 μg/ml of BSE-SLNp potentially enhanced antioxidant capacity, cell growth and microtubule development within 48hr. H2O2 induced oxidative stressed HUVECs shown 39.8 % viable cells, but treatment with BSE-SLNp shown 99% of viable cells within 48 hr confirmed by Annexin-V assay. In addition, mitochondrial membrane potential (Δψm) increased to 89.4% confirmed by JC-1 assay. The observed DNA integrity, cell viability was confirmed by increased antioxidant and tumor suppressor-related gene expression levels. VEGF expression has been significantly increased and pro-inflammation-related mRNA levels were decreased in BSE-SLNp treated cells. In conclusion, enhanced adipocyte fatty acid oxidation is directly associated with decreased adipocytokine secretion which arrests obesity-associated comorbidities. In addition suppressing vascular cell oxidative stress and metabolic inflammation supports vascular cell proliferation and arrest ageing-related vascular diseases.